THE TENDENCIES OF GLOBALIZATION AND REGIONALIZATION OF CIVIL PROCEDURAL LAW IN THE COUNTRIES COMPRISING THE COMMUNITY OF INDEPENDENT STATES - Terekhov, Victor (Teisė, 2015)
The article deals with the current situation in the field of Civil Procedure approximation in the Community of Independent States (CIS) countries and the perspectives of further regional and worldwide harmonization and unification of this branch there. As the comparative object, the law of the European Union is taken, the Member States of which managed to achieve a certain progress in the field of development of common Civil Procedure.